Highly efficient synthesis of aryl ketones by PEPPSI-palladium catalyzed acylative Suzuki coupling of amides with diarylborinic acids. Issue 23 (6th June 2018) - Wang, Chen; Huang, Lingyun; Wang, Fengze; Zou, Gang
Graphical abstract: Highlights: Highly efficient acylative Suzuki coupling of diarylborinic acids. Practical synthesis of aryl ketones in excellent yields. Readily prepared and cost-effective substrates. Commercially available catalyst. Wide substrate scope. Abstract: An improved acylative cross-coupling of various N -methyl- N -tosyl amides with diarylborinic acids for synthesis of aryl ketones is developed. In most cases, aryl ketones could be obtained in excellent yields by using 1 mol% 2, 6-diisopropylphenylimidazolylidene and 3-chloropyridine co-supported palladium chloride as catalyst in the presence of 3 equiv. K2 CO3 as base in refluxing THF. The readily prepared and cost-effective substrates, N -methyl- N -tosylamides and diarylborinic acids, and the commercially available catalyst system promise a practical and efficient access to aryl ketones.